Klasifikasi dan Edukasi Alternatif Media Pembelajaran Daring untuk Edukator - Maidel Fani; Nelmiawati Nelmiawati; Ahmad Hamim Thohari; Hamdani Arif; Supardianto Supardianto; Muchammad Fajri Amirul Nashrullah; Dodi Prima Resda; Heru Wijanarko; Rizky Pratama Hudhajanto; Dwi Ely Kurniawan; Rina Yulius; Mira Chandra Kirana; Muhammad Idris (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
Abstract—Corona Virus Diseases 2019 (COVID-19) has been spread and infected many people in the world. Government issued physical distancing policy and ordered schools and colleges to conduct an online learning to overcome the spread. A transition from conventional to online learning poses new problems such as unpreparedness of educators and students to comply on this situation. One of the factors of unpreparedness is the uneven spread of the internet so that students find it difficult to follow the online learning process. Therefore, there needs to be a proper alternative media selector by educators so that in the delivery of material can be followed by all students. Education about the selection of alternative media online is expected to be a solution for educators in determining the media and methods chosen according to the conditions faced. In general, the results of questionnaire analysis that has been disseminated provide new benefits and knowledge for educators about alternative media online learning process. Thus, educators can determine which media and methods to choose based on their individual circumstances and situations